THE EFFECT OF WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL COMMITMENT - Leoni Ginting; Galeh Sari (Journal of Financial Management & Accounting, 2025)
The company requires mutual commitment between the organization and employees so that they can jointly realize the company's goals and desires. Good employee management will certainly foster good organizational commitment of employees as well. The method used in this research is quantitative descriptive. The population and sample of this study were all employees, amounting to 75 people. Questionnaire processing is measured with a Likert scale. The data analysis model used to answer hypotheses is multiple linear regression analysis. The results showed that partially and simultaneously work motivation and organizational culture had a positive and significant effect on organizational commitment. The most dominant variable influencing organizational commitment is work motivation. Keywords: Work Motivation, Organizational Culture, Organizational Commitment.